Comparative Study between Linear-Interpolation and Stress-Block Methods of Composite Design Using Cold-Formed Steel Section - M. Lawan, M; N. Shek, P; M. Tahir, M (International Journal of Engineering and Technology, 2018)
For decades, Hot Rolled Steel (HRS) section was in use in construction of buildings and bridges. The simple reason is that the use of HRS section in composite systems is well established by standard rules and their design necessities as provided in the codes. In this paper, the use of doubly oriented back-to-back Cold-Formed Steel (CFS) section coupled with bolted shear connectors in composite floor system was demonstrated. The bolted system of shear connector provides an alternative to headed stud shear connector with CFS section as welding of the stud connector is practically not feasible on CFS section because of its thinness nature. The loading system used was four-point bending test to determine the flexural strength capabilities of the composite floor system. The resulting composite floor system has proven to provide adequate strength and stiffness properties under the applied loads. The results have shown that the theoretical value of flexural capacities calculated agrees reasonably well with the experimental values. In conclusion, the composite floor system can be used in small and medium size buildings, as well as in light weight construction industries.Â Â  Â